Update on thrombolytic therapy in ischemic stroke - Hacke, Werner; Willig, Vera; Steiner, Thorsten (Fibrinolysis & proteolysis, 1997)
The principal goal of thrombolytic therapy for stroke is to achieve early restitution of cerebral blood flow, reduction of ischemia and limitation of neurological disability through lysis of an occluding thrombus and consequent rapid restoration of circulation in the affected territory. This survey will focus on the safety and efficacy of angiographic clinical trials of thrombolytic therapy in acute ischemic stroke. Initiation of therapy should take place as early as possible, at least within 4-6 h after stroke to prevent major infarction and to salvage the hypoperfused but potentially viable zone adjacent to the central ischemic area known as the ischemic penumbra. Recently, the results of two successful major randomized studies using tissue plasminogen activator (tPA) have been published. The use of tPA is now approved in the United States. Intravenous thrombolysis seemed to be effective to improve functional and neurological outcome in a clearly defined subgroup of patients meeting the inclusion criteria of the study. However, the identification of those patients proved to be difficult and depended on the expertise to recognize the early infarction signs on the initial CT. Therefore, since treating the ineligible patients is associated with an unacceptable risk of intracranial bleeding complications and death, intravenous thrombolysis should only be performed at selected centers for selected patients.
Elektronische Reproduktion der Druck-Ausgabe 9. Juni 2005
Gesehen am 28.05.2025